ANALISIS SINERGITAS TARIK ULUR KEPENTINGAN DALAM PRODUKSI PERTANIAN DAN JASA LINGKUNGAN - Agustinus JP Ana Saga (Agriculture Faculty of Flores University, 2018)
Synergi analysis of the tugging of interest in agricultural production and envirometal services. Conversion of land functions into intensive agriculture can cause degradation or declining land capability. This is because farmers' orientation is always on production and ignoring environmental services. Intensive agriculture always causes environmental problems, resulting in a tug of war in agricultural production and environmental services. The purpose of this study is to find out how much intensive land use has resulted in a deterioration of environmental services. This research was carried out on intensive agricultural land (Horticulture) (PI), AF-CK (cloves), AF-KK (cocoa), AF-KM (candlenut), AF-KP (coffee), owned by farmers and AF-HS (forest secondary) in Tn. Kelimutu National. This research uses interviews and exploration methods. The results showed that the level of intensification of horticultural land use in Kelimutu was classified as very intensive with an R-value and an LUI index = 79, the survey results showed that the density of earthworm populations in SPL-AF was as low as the population in SPL-HS, on average only 3 tails m-2, while in SPL-PI the average is only 0.24 m 2. The earthworm biomass in AF is about 69% smaller than the worms found in SPL-HS; earthworm biomass average in SPL-AF 15 g m-2 while in SPL-HS an average of 47 g m-2; and the smallest worm biomass found in SPL-PI averaging about 2.3 g m-2. The diversity of earthworms is significantly different between land uses. The average diversity of earthworms (H ') reaches 0.88; Index R = 0.34; and Index E = 0.92. The four species that dominate are 1). Pontoscolex (endogeik, INP = 48.52), 2). Megascolex (endogeik; INP 44,61), 3). Pheretima (epigeic, INP 35.29), and 4). Lumbricus (epigeic, INP = 13.01)